Measurement and prediction of water-energy-food-economy-ecology coupling coordination degree in Shandong Province, China - Chenjun Zhang; Man Li; Xiangyang Zhao; Yuze Wang; Keyi Ju (Ecological Modelling, 2026)

Shipowners’ responses to carbon tax: speed optimization using AIS data - Hailing Liu; Keyi Ju; Xiaozhuo Wei; Chenjun Zhang; Jianghang Zhou (Clean Technologies and Environmental Policy, 2025)

Theory and practice of China’s shipping carbon tax under the “dual carbon” targets - Hailing Liu; Keyi Ju; Meirong Guo; Tianlin Mao (Frontiers in Marine Science, 2025)
The issue of emissions reduction in the shipping industry has garnered widespread attention from the international community. The International Maritime Organization and many countries have been exploring market-based emission reduction measures such as the carbon tax. Given China’s pivotal role in international maritime trade, developing effective carbon reduction policies is essential for the nation and the broader decarbonization of global shipping. To establish a shipping carbon tax system tailored to China’s context, it is imperative to draw upon international practices while grounding the framework in the realities of China’s market economy and the specifics of its shipping industry. Following the overarching requirement of coordinated international and domestic advancement, this study clarifies the design principles and basis for a carbon tax on shipping. Building on this analysis, policy recommendations are proposed for China’s adoption of such a tax. The findings aim to provide theoretical support for subsequent research on energy conservation and emissions reduction in the shipping industry, leveraging the role of the shipping carbon tax in achieving the “dual carbon” targets.

Biochar-influenced solubilization and mineralization mechanisms of phosphorus in saline-sodic soils - Lei Chang; Tianhang Ju; Keyi Liang; Yuefen Li (Soil Biology and Biochemistry, 2025)

Water–Energy–Land Reallocation and Multiobjective Optimization in the Agricultural System - Jue Wang; Keyi Ju; Xiaozhuo Wei (Water Resources Management, 2024)

Microplastics sequestered in the soil affect the turnover and stability of soil aggregates: A review - Tianhang Ju; Kai Yang; Lei Chang; Keyi Zhang; Xingyi Wang; Jialin Zhang; Bo Xu; Yuefen Li (Science of The Total Environment, 2023)

A comprehensive evaluation of the security of the water-energy-food systems in China - Keyi Ju; Jue Wang; Xiaozhuo Wei; Hao Li; Siyang Xu (Sustainable Production and Consumption, 2023)